Subsurface drip irrigation of ladies finger in sandy loam soil - NISHA T. V; Er. Asha Joseph (Guide) (Tavanur 2007 Kelappaji College of Agricultural Engineering and Technology)
Subsurface drip irrigation of ladies finger in sandy loam soil
Subsurface drip irrigation of ladies finger in sandy loam soil